The Strategic Role of Artificial Intelligence in Integrating Customer Relationship Management and Retail Operations - Usman, Maulana; Putra, Kukuh Ramadhan Sukma; Yuniawan, Ahyar; Djastuti, Indi (Economic and Business Horizon, 2025)
Artificial Intelligence has become a key driver in the transformation of the retail industry, particularly in customer relationship management, records management, and warehouse automation. This research aims to examine the strategic role of Artificial Intelligence in integrating these thre aspects to improve operational efficiency and business competitiveness. Using the literature study method, this article analyzes nine scholarly articles that discuss Artificial Intelligence implementation in related sectors. The results show that Artificial Intelligence significantly contributes to the personalization of customer service, automated data management, and optimization of logistics processes. However, Artificial Intelligence implementation also faces challenges, including large investment requirements, complex system integration, and organizational resistance to change. This study concludes that an integrated and strategically designed Artificial Intelligence implementation can provide retail companies with a sustainable competitive advantage in the digital era. The study also recommends the need for a more adaptive approach and investment in internal capacity building to maximize the benefits of Artificial Intelligence in the retail industry.